Role of community participation in achieving low carbon lifestyles in Kuala Lumpur - Basri, Nek Mah; Sharaai, Amir Hamzah; Arsyad, Mohd Mursyid; Ponrahono, Zakiah (e-International Publishing House, 2024)
This paper examines community engagement in Kuala Lumpur's Low Carbon Lifestyle (LCL) programs, led by Local Agenda 21 Kuala Lumpur (LA21KL). It investigates how community participation can drive the city's goal to achieve zero carbon emissions by 2050. The study identifies three key themes based on qualitative research and in-depth interviews: empowering community participation, strengthening engagement in low programs, and green urban governance. This study emphasises the importance of raising awareness about the benefits of LCL programs to boost community involvement. Strategies like fostering local champions are essential for successfully implementing these initiatives.